Split Hopkinson Pressure Bar Multiple Reloading and Modeling of a 316 L Stainless Steel Metallic Hollow Sphere Structure - Taşdemirci, Alper; Ergönenç, Çağrı; Güden, Mustafa; Güden, Mustafa; Taşdemirci, Alper (Elsevier Ltd., 2010)
The high strain rate (600 s−1) compression deformation of a 316 L metallic hollow sphere (MHS) structure (density: 500 kg m−3; average outer hollow sphere diameter: 2 mm and wall thickness: 45 μm) was determined both numerically and experimentally. The experimental compressive stress–strain behavior at high strain rates until about large strains was obtained with multiple reloading tests using a large-diameter compression type aluminum Split Hopkinson Pressure Bar (SHPB) test apparatus. The multiple reloading of MHS samples in SHPB was analyzed with a 3D finite element model using the commercial explicit finite element code LS-DYNA. The tested MHS samples showed increased crushing stress values, when the strain rate increased from quasi-static (0.8 × 10−4 s−1) to high strain rate (600 s−1). Experimentally and numerically deformed sections of MHS samples tested showed very similar crushing characteristics; plastic hinge formation, the indentation of the spheres at the contact regions and sphere wall buckling at intermediate strains. The extent of micro-inertial effects was further predicted with the strain rate insensitive cell wall material model and with the strain rate sensitive behavior of MHS structure similar to that of the cell wall material. Based on the predictions, the strain rate sensitivity of the studied 316 L MHS sample was attributed to the strain rate sensitivity of the cell wall material and the micro-inertia.
Keywords: Metallic hollow sphere; Split Hopkinson Pressure Bar; High strain rate; LS-DYNA; Multiple loading